2003
DOI: 10.1242/dev.00530
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Bmp7 and Fgf8 signaling in Hoxa13-mutant mice causes hypospadia

Abstract: In humans and mice, mutations in Hoxa13 cause malformation of limb and genitourinary (GU) regions. In males, one of the most common GU malformations associated with loss of Hoxa13 function is hypospadia,a condition defined by the poor growth and closure of the urethra and glans penis. By examining early signaling in the developing mouse genital tubercle,we show that Hoxa13 is essential for normal expression of Fgf8 and Bmp7 in the urethral plate epithelium. In Hoxa13GFP-mutant mice, hypospadias occur as a resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
184
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(192 citation statements)
references
References 69 publications
6
184
0
1
Order By: Relevance
“…in the development of the phallus since knock-out of these genes in mice induces a malformation in the external genitalia consistent with hypospadias [23]. In humans, the hand-foot-genital syndrome (HFGS) [24,25] …”
Section: -Level Of Phallus Development: Homeobox Genes a (Hoxa) And mentioning
confidence: 99%
“…in the development of the phallus since knock-out of these genes in mice induces a malformation in the external genitalia consistent with hypospadias [23]. In humans, the hand-foot-genital syndrome (HFGS) [24,25] …”
Section: -Level Of Phallus Development: Homeobox Genes a (Hoxa) And mentioning
confidence: 99%
“…The phenotypes of gene knockout mice have revealed that several growth and signaling factor families play fundamental roles in reproductive and urogenital organ formation (Batourina et al, 2002;Doles et al, 2006;Haraguchi et al, 2001;Haraguchi et al, 2000;Huang et al, 2005;Jamin et al, 2002;Kobayashi and Behringer, 2003;Kondo et al, 1996;McMahon et al, 2003;Morgan et al, 2003;Perriton et al, 2002;Suzuki et al, 2003). Shh is expressed in the cloacal epithelia and is vital for the regulation of structures derived from the genital tubercle (GT) and the urogenital sinus, such as the external genitalia and the prostate, respectively (de Santa Barbara and Roberts, 2002;Freestone et al, 2003;Pu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true of 5Ј HoxA and HoxD genes, which are involved in limb patterning (reviewed in references 49 and 65). The inactivation of the Hoxd13 gene in mice, for instance, causes a phenotype resulting from defects in the proliferation and/or condensation of limb mesenchymal cells (11,14).Hox proteins have been shown to act as transcription factors, which are thought to regulate sets of target genes by binding to specific DNA sequences within the transcriptional regulatory regions of these (7,33,38,43,50,51,61,62). Recent findings, however, have hinted at a possible additional function for this family of DNA-binding proteins.…”
mentioning
confidence: 99%
“…Hox proteins have been shown to act as transcription factors, which are thought to regulate sets of target genes by binding to specific DNA sequences within the transcriptional regulatory regions of these (7,33,38,43,50,51,61,62). Recent findings, however, have hinted at a possible additional function for this family of DNA-binding proteins.…”
mentioning
confidence: 99%